The dominicans and the indigenous peoples of Madre de Dios: Documentary study - Dávila Francia, Jesús Taylor (2021)
Begun in the late 1990s, this research aims to identify the arrival of the evangelists to the Amarakaeris people. The newspaper "El Comercio" was the first source of information, afterwards "La Revista Dominicana" and the magazine of the "Sociedad Geográfica de Lima" were reviewed, ending with other possibilities. The role of the Dominican congregation is not too far of the evangelism and colonisation process around America, and the world by other sects. The removal of idolatries was the most used implement notwithstanding, the past and current Press attempt to make the Dominican Fathers look like saviours of soulless natives. The other form of violence was even more open and miserable: the rubber boom with Fitzcarrald in command. In one way or the other two different worldviews faced each other in disadvantage. It is been proven that the fantasy, myths, and legends take their origin from a context and determined reality, and in the villages in Madre de Dios did not exist the idea of Saints, Virgins and archangels before the arrival of the evangelists and colonisers. These were not part of the worldview of our Amazonian peoples at all. This process conducted between the native groups of the alluded region took part of a world plan for evangelism and colonisation.